Domain-based key management for heterogeneous wireless sensor networks - MA Chun-guang; SHANG Zhi-guo; WANG Hui-qiang (Tongxin xuebao)
Key management was one of the most challenging security problems in wireless sensor networks. Based on the random key pre-distribution scheme, a new scheme was proposed for heterogeneous wireless sensor networks using deployment knowledge of the node and the prior area deployment information. The performance evaluation and security analysis show that compared with existing key management schemes, the key management scheme can substantially improve a network’s connectivity with low complexity, significantly reduce the storage requirement and enhance the network resilience against node capture.